Integrating Normative-Theological and Sufi-Spiritual Approaches in Contemporary Islamic Studies: A Critical Methodological Analysis - Ahmad, Nurhadi; Yuharniza, Yuharniza; Hidayat, Moh. Arief; Wahyuni, Sri; Hakim, Rosniati (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
Islamic Studies as an academic discipline faces methodological challenges in responding to the complexity of contemporary realities. This article critically examines two dominant approaches in Islamic Studies, namely the normative-theological approach and the Sufi-spiritual approach. The normative-theological approach emphasizes textual authority through classical Islamic scholarly methodologies, while the Sufi-spiritual approach focuses on inner experience and spiritual transformation. This study employs a qualitative method using content analysis of the perspectives of eight Islamic Studies scholars published between 2022 and 2023. The findings reveal methodological polarization between the two approaches, while also identifying an emerging integrative trend that seeks to bridge the tension between textual authority and spiritual experience. This article argues that the development of an integration–interconnection paradigm constitutes a significant epistemological contribution to contemporary Islamic Studies. The findings have implications for the development of integrative curricula, dialogical methodologies, and the strengthening of a more holistic Islamic epistemology.